Selenocysteine as a Substrate, an Inhibitor and a Mechanistic Probe for Bacterial and Fungal Iron‐Dependent Sulfoxide Synthases. Issue 6 (20th January 2020) - Goncharenko, Kristina V.; Flückiger, Sebastian; Liao, Cangsong; Lim, David; Stampfli, Anja R.; Seebeck, Florian P.
Abstract: Sulfoxide synthases are non‐heme iron enzymes that participate in the biosynthesis of thiohistidines, such as ergothioneine and ovothiol A. The sulfoxide synthase EgtB from Chloracidobacterium thermophilum ( Cth EgtB) catalyzes oxidative coupling between the side chains of N ‐α‐trimethyl histidine (TMH) and cysteine (Cys) in a reaction that entails complete reduction of molecular oxygen, carbon–sulfur (C−S) and sulfur–oxygen (S−O) bond formation as well as carbon–hydrogen (C−H) bond cleavage. In this report, we show that Cth EgtB and other bacterial sulfoxide synthases cannot efficiently accept selenocysteine (SeCys) as a substrate in place of cysteine. In contrast, the sulfoxide synthase from the filamentous fungus Chaetomium thermophilum ( Cth Egt1) catalyzes C−S and C−Se bond formation at almost equal efficiency. We discuss evidence suggesting that this functional difference between bacterial and fungal sulfoxide synthases emerges from different modes of oxygen activation. Abstract : Sulfoxide synthases : Bacterial and fungal iron‐dependent sulfoxide synthases are distinguished by their different abilities to catalyze oxidative carbon–selenium bond formation.